Modified Suction-Effective denture technique for mandibular flat ridge - Joewana, Clinton ST.; Lindawati S. Kusdhany (Indonesia Prosthodontic Association, 2025)
Aging is a universal, progressive physiological process affecting all living organisms, leading to the loss of bone, bone mineral density, and muscle in humans. The rate and extent of musculoskeletal decline vary due to factors such as diet, systemic diseases, medications, and clinical interventions. Prolonged denture use can lead to atrophy of the residual alveolar ridge, particularly in cases of a flat mandibular ridge, where achieving adequate denture retention and stabilization is challenging. Proper impression techniques play a crucial role in addressing this challenge. This report aims to describe the management of complete dentures in cases of mandibular flat ridges using a modified suction-effective method. A 70-year-old female presented for a complete denture following the extraction of her last upper left tooth. She had previously used removable partial denture around 3 years ago but has not used them since. Clinical findings revealed significant bone loss in the mandible, sufficient spongy tissue on the sublingual area, and panoramic examination classified the mandibular cortical index and bone density as C2. A centric tray was used to record the vertical dimension to fabricate the bite rim used for closed-mouth impression. Lingualized occlusion scheme was then used during denture fabrication to achieve a more stable denture. The suction-effective denture is an enhanced method for achieving retention and stability in patients with flat mandibular ridge. Creating a good peripheral seal on all borders is crucial to achieve the suction effect, which can be facilitated through proper planning and impression technique. Keywords: mandibular flat ridge, suction denture, suction-effective method, closed-mouth impression